2017
DOI: 10.1103/physrevapplied.7.054002
|View full text |Cite
|
Sign up to set email alerts
|

Control of Synchronization Regimes in Networks of Mobile Interacting Agents

Abstract: We investigate synchronization in a population of mobile pulse-coupled agents with a view towards implementations in swarm-robotics systems and mobile sensor networks. Previous theoretical approaches dealt with range and nearest-neighbor interactions. In the latter case, a synchronization-hindering regime for intermediate agent mobility is found. We investigate the robustness of this intermediate regime under practical scenarios. We show that synchronization in the intermediate regime can be predicted by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Similarity between the periods of the units is crucial to achieve such a synchronized state but there is another ingredient that plays also a very significant role: the pattern of interactions between the units [4][5][6]. It is important not only for determining the time scale to reach a stationary state but in some cases-as in the situation under study in the present work-it can even prevent the synchronization of identical units [7,8].…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Similarity between the periods of the units is crucial to achieve such a synchronized state but there is another ingredient that plays also a very significant role: the pattern of interactions between the units [4][5][6]. It is important not only for determining the time scale to reach a stationary state but in some cases-as in the situation under study in the present work-it can even prevent the synchronization of identical units [7,8].…”
Section: Introductionmentioning
confidence: 92%
“…In particular, more recent works [8,20] have confirmed that a sparse and nonreciprocal interaction pattern is a necessary condition for such behavior to be observed, yet the validity of the general interpretation based on the two time scales has not been verified.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations